Ergonomic Evaluation of Anthropometry Based Hydroponic Plants Watering Automation System - Suradi; Hanafie, Ahmad; Haslindah, Andi; Bora, M. Ansyar; Baco, Syarifuddin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Hydroponics is a technique of growing plants without soil. Until now, many people do it manually for moisture, content, nutrition, and continuous flow of water. The application of ergonomics aims to make the user healthy, comfortable, safe, productive. The purpose of evaluating anthropometry-based ergonomics, and testing the hydroponic plant watering automation system tool. The method used is collecting anthropometric data on the dimensions of the user's body for ergonomics, then designing an automatic hydroponic watering tool to make it easier to design hardware and software. The results of the ergonomics evaluation study, hand span size 175.3 cm, upright body height 167.4 cm, shoulder to head 32.23 cm, shoulder to base of foot 66.77 cm, base of foot to knee 48.89 cm, base of foot to knee 48.98 cm, elbow to elbow 41.81 cm, elbow to hand 34.45 cm. While the results of testing the condition of the charcoal are at the humidity threshold of 49% - 60% then the pump will be on, and if the pot has been on the humidity threshold of 65% - 99% then the pump will be off.